Protocolo para la práctica clínica de visión binocular y acomodación (2021)
Taking into account that a protocol is a document that compiles a series of specific procedures for the development of a health care process (1), this application document for the clinical practice of binocular vision and accommodation is presented for the Faculty of Optometry from the Antonio Nariño University